Initial results of an optimized perfusion system. (July 2013) - Starck, CT; Bettex, D; Felix, C; Reser, D; Dreizler, T; Hasenclever, P; Falk, V
Background: In order to reduce the negative effects of extracorporeal circulation (ECC), the perfusion system and management were optimized at our institution. The goals of optimization were a reduction in the priming volume, in the foreign surface area and in microbubble activity, as well as optimization of suction blood management. Methods: Sixty patients were included in this retrospective study. Patients were assigned to two groups, with regard to the use of an optimized perfusion system (OPS-group, n=30) and a standard perfusion system (SPS-group, n=30). All patients underwent elective procedures. Results: There were no significant differences with respect to patient demographics and operation time. ECC time and cross-clamp time were significantly longer in the OPS group. Statistically significant differences in outcome between the two groups were seen with regard to the following variables: effective priming volume (OPS: 775±447ml; SPS: 1610±0ml; p<0.0001), hemoglobin drop after the start of ECC (OPS: 2.7±1.2g/dl; SPS: 4.2±0.8g/dl; p<0.0001), c-reactive protein on postoperative day 2 (OPS: 121.0±59.4 U/l; SPS: 164.0±50.2 U/l; p=0.003). With regard to the use of blood transfusions, a 33% reduction in the overall amount of transfused units was seen. The rate of patients without transfusions during the entire hospital stay increased from 37% (SPS) to 53% (OPS). The mean transfused red blood cell units per patient was lower in the OPS-group (1.6±2.4 units) than in the SPS-group (2.3±3.5 units). Conclusion: With the described optimized perfusion system, a significantly lower priming volume, leading to less hemodilution after the onset of CPB, was achieved. The amount of blood transfusions and the inflammatory response were reduced.